High Brightness 2.2–12 μm Mid‐Infrared Supercontinuum Generation in a Nontoxic Chalcogenide Step‐Index Fiber. Issue 8 (29th June 2016) - Zhang, Bin; Yu, Yi; Zhai, Chengcheng; Qi, Sisheng; Wang, Yuwei; Yang, Anping; Gai, Xin; Wang, Rongping; Yang, Zhiyong; Luther‐Davies, Barry
Abstract : An environment friendly nonlinear chalcogenide glass fiber with a Ge‐Sb‐Se core and a Ge‐Se cladding is fabricated for bright broadband mid‐infrared (MIR) supercontinuum (SC) generation. The fabricated Ge‐Sb‐Se/Ge‐Se fiber with a core diameter of 6 μm shows zero group velocity dispersion at 4.2 μm and 7.3 μm. By pumping the fiber with a length of 11 cm at 4.485 μm with 330 fs pulses, we achieve a SC covering the 2.2–12 μm spectral range and with an output average power of 17 mW. This bright broadband SC source is promising for high‐resolution MIR spectroscopy.